2018
DOI: 10.1016/j.ymthe.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Serve as Nanoparticles to Deliver Anti-miR-214 to Reverse Chemoresistance to Cisplatin in Gastric Cancer

Abstract: Chemoresistance is one of the causes of adverse effects in gastric cancer, including a poor response to cisplatin (DDP). Exosomes loaded with microRNA (miRNA), mRNA, and other non-coding RNAs could regulate drug resistance. Exo-anti-214 was extracted and verified. A Cell Counting Kit-8 (CCK-8) cell viability assay, flow cytometry, and transwell and immunofluorescence assays were performed to determine whether exo-anti-214 could sensitize cells to DDP in vitro. A combination of intravenously injected exo-anti-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 39 publications
1
122
0
Order By: Relevance
“…Interestingly, the study proved the crucial role of the apolipoprotein E (ApoE), an M2-specific and highly rich protein derived from M2 exosomes, in determining the migration potential of GC cells [80]. Wang X. et al reported an in vitro investigation performed on HEK293T cells, which proves that exosomes represent efficient nanovectors for the delivery of anti-miR-214, and are thus able to reverse chemoresistance to cisplatin in GC [81]. An in vitro and in vivo study demonstrated that, after HEK293T cell transfection with hepatocyte growth factor (HGF) siRNA, the cell secreted exosomes containing HGF siRNAs that inhibited the proliferation and migration of cancer cells in GC [82].…”
Section: Cancer-derived Exosomes As Drug Delivery Vehicles For the Trmentioning
confidence: 99%
“…Interestingly, the study proved the crucial role of the apolipoprotein E (ApoE), an M2-specific and highly rich protein derived from M2 exosomes, in determining the migration potential of GC cells [80]. Wang X. et al reported an in vitro investigation performed on HEK293T cells, which proves that exosomes represent efficient nanovectors for the delivery of anti-miR-214, and are thus able to reverse chemoresistance to cisplatin in GC [81]. An in vitro and in vivo study demonstrated that, after HEK293T cell transfection with hepatocyte growth factor (HGF) siRNA, the cell secreted exosomes containing HGF siRNAs that inhibited the proliferation and migration of cancer cells in GC [82].…”
Section: Cancer-derived Exosomes As Drug Delivery Vehicles For the Trmentioning
confidence: 99%
“…The strategies described above to load EVs with proteins by engineering of the parent cells can be applied also in the case of nucleic acids. For instance, to reverse the chemoresistance to cisplatin-refractory gastric cancer, human embryonic kidney 293T (HEK-293T) cells are transfected with anti-miR-214 and the produced vesicles are administered systemically in combination with cisplatin, injected intraperitoneally, to overcome the in vitro and in vivo drug-resistance [165]. EVs produced by miR-134 or anti-miR-21 transfected mammary carcinoma cells have the ability to reduce the cellular proliferation and migration and to enhance the apoptosis in breast cancers [121,166].…”
Section: Indirect Loadingmentioning
confidence: 99%
“…These EVs allowed to track the cell-cell communication and also perform the optical hyperthermia for cancer therapy [181]. Exosomes from HEK 293T miR-21 sponges Therapy for leukemia cells [174] Extracellular vesicles from breast cancer Anti-miR-21 Theranostic method for breast cancer [121] Exosomes from HEK 293T Inhibitor of miR-214 Reverse chemoresistance to cisplatin in gastric cancer [165] Exosomes from prostate cancer cells Anti-miR-21 spherical nucleic acid Prostate cancer [155] Exosomes from mammary carcinomas miR-134 Increase sensitivity of breast cancers to chemotherapeutic drugs [166] Exosomes from mesenchyme stem cells miR-122 Increase sensitivity of hepatocellular carcinoma to chemotherapeutic drugs [167] Exosomes from mesenchymal stem cells miR-143 Inhibit migration of osteosarcoma cells [169] Exosomes from mesenchymal stem cells anti-miR-9…”
Section: Indirect Loadingmentioning
confidence: 99%
“…To support this possibility, one study transfected inhibitors of miR-214 and a negative control into HEK293T cells, and exosomes extracted from the cell medium after 48 h were verified to contain the inhibitor of miR-214, which reversed the resistance to DDP both in GC cells and in vivo. 10 In applications for reversing drug resistance or directly suppressing tumors, exosomes containing mimics or inhibitors of miRNAs are likely safer than synthetic nanoparticles and compounds. However, more research is needed to solve exosome-related technical problems, such as the lack of methods to interfere with the packaging of cargo or with vesicle release, before microRNA-based targeted therapies can become a reality.…”
Section: Exosomesmentioning
confidence: 99%
“…9 Moreover, caudally injected exosomes loaded with the inhibitor of miR-214 (exo-anti-214) could reverse the chemoresistance to cisplatin in a nude mouse model of GC. 10 In addition, synthetic carriers have been used to deliver the confirmed anti-tumor miRNAs to the precise tumor site so as to directly inhibit GC, such as "PPP", which was constructed by modifying phenylboronic acid onto the surface of a polyamidoamine dendrimer and poly (ethylene glycol)-poly(ε-caprolactone) copolymers (PEG-PCL) nanoparticles coated with trastuzumab. 11,12 Indeed, these studies have led to a major advance in the clinical application of miRNAs.…”
Section: Introductionmentioning
confidence: 99%